Kontakty językowe i komunikacja w środowisku audiofilów = Language contacts and communication in an audiophile community - Kładoczny, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns language contacts and communication in an audiophile milieu. Audiophiles are people who have a passion for audio equipment which produces top quality sound. Audiophiles are mainly men. They do not function like formalized groups or ssociations.
Keywords: audiofil; kontakty językowe; komunikacja; audiophile; language contacts; communication